1988
DOI: 10.1007/bf00398183
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of androgen and antiandrogen on the in vitro proliferation of human mammary carcinoma cells

Abstract: The proliferation of three mammary carcinoma cell lines was explored for the effectiveness of dihydrotestosterone (DHT) and the antiandrogenic substances cyproterone acetate (CPA) or hydroxyflutamide. The cell growth, determined in multiple experimental cultures of the estrogen-sensitive lines MCF-7 and EFM-19, was stimulated by 10(-9) M to 10(-6) M DHT, whereas estrogen-resistant MFM-21 cells were unresponsive to the hormonal factors applied. Growth-promoting effects of 10(-8) M to 10(-6) M CPA were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The mechanism of testosterone action in the female breast is still unclear as well as whether the eVects are predominantly proliferative or anti-proliferative on breast cells at physiologic levels. In contrast to the epidemiologic observation of a consistent association between serum testosterone levels and increasing breast cancer risk (Wysowski et al 1987;Garland et al 1992;Dorgan et al 1996;Berrino et al 1996;Thomas et al 1997;Zeleniuch-Jacquotte et al 1997;Hankinson et al 1998;Cauley et al 1999), in vivo studies reported an anti-proliferative eVect (Zava and McGuire 1977), and in vitro studies reported both proliferative (Poulin et al 1988;Ortmann et al 2002) and anti-proliferative eVects (Hackenberg et al 1988;Marugo et al 1992).…”
Section: Introductionmentioning
confidence: 75%
“…The mechanism of testosterone action in the female breast is still unclear as well as whether the eVects are predominantly proliferative or anti-proliferative on breast cells at physiologic levels. In contrast to the epidemiologic observation of a consistent association between serum testosterone levels and increasing breast cancer risk (Wysowski et al 1987;Garland et al 1992;Dorgan et al 1996;Berrino et al 1996;Thomas et al 1997;Zeleniuch-Jacquotte et al 1997;Hankinson et al 1998;Cauley et al 1999), in vivo studies reported an anti-proliferative eVect (Zava and McGuire 1977), and in vitro studies reported both proliferative (Poulin et al 1988;Ortmann et al 2002) and anti-proliferative eVects (Hackenberg et al 1988;Marugo et al 1992).…”
Section: Introductionmentioning
confidence: 75%
“…1C). In interpreting these results, it is worth noting that these authors (Wang et al 2013a,b) report an anti-proliferative effect of androgen treatment in these cell lines, in contrast to a number of other studies that report proliferative effects of androgen (Hackenberg et al 1988, Maggiolini et al 1999, Birrell et al 1995, Ni et al 2011, Robinson et al 2011. Although the reasons for these discrepancies are unknown, this indicates the potential for dualistic effects of AR signalling in MDA-MB-453 and MCF7 breast cancer cell lines.…”
Section: Ar Pten P53 and Pi3k/aktmentioning
confidence: 86%
“…However, divergent responses to androgens are seen in different human breast cancer cell lines. For example, androgens may stimulate (MCF-7, EFM-19, EVSA-T, MDA-MB-453) or inhibit (T-47D, ZR-75-1, MFM-223) the growth of AR-positive breast cancer cell lines in vitro (Birrell et al, 1995a;Hackenberg et al, 1988Hackenberg et al, , 1991Hall et al, 1994;Marugo et al, 1992;Poulin et al, 1988). This divergent proliferative response to androgens may in part be due to alterations in the AR gene, resulting in altered receptor function and activation of androgen-regulated genes (Berger and Watson, 1989), or interaction between AR and other steroid receptors [e.g.…”
mentioning
confidence: 99%